Clusterin suppresses spermatogenic cell apoptosis to alleviate diabetes‐induced testicular damage by inhibiting autophagy via the PI3K/AKT/mTOR axis. (4th November 2020) - Tian, Yuan; Xiao, Yue‐Hai; Geng, Tian; Sun, Chao; Gu, Jiang; Tang, Kai‐Fa; Liu, Bei; Liu, Yi‐Meng; Sun, Fa
Abstract : Background information: Diabetes‐induced testicular dysfunction is characterised by abnormal apoptosis of spermatogenic cells, but the underlying mechanism is poorly understood. This study aimed to investigate the roles of clusterin (CLU) in testicular damage associated with diabetes pathogenesis, as well as the molecular mechanism. A rat diabetes model was established using streptozocin, and the mouse spermatogenic cell line GC‐1 spg was treated with high glucose as a cellular model. CLU was overexpressed in GC‐1 spg cells, followed by detection of serum testosterone, cell proliferation, cell apoptosis and autophagy. Results: CLU expression was significantly reduced and LC3 expression was elevated in testis tissues in the rat diabetes model and high glucose‐treated GC‐1 spg cells. High glucose led to suppressed viability, enhanced apoptosis, reduced Bcl‐2 expression, elevated Bax expression and cleavage of Caspase‐3/‐9 in GC‐1 spg cells, and these effects were abrogated by CLU overexpression. Additionally, CLU overexpression repressed LC3 and Beclin‐1 expression, reduced the LC3II/LC3I ratio and promoted p62 expression in GC‐1 spg cells in the presence of high glucose, and these effects were all mitigated by rapamycin treatment. Inhibition of PI3K/AKT/mTOR signalling with LY294002 activated autophagy in CLU‐overexpressing GC‐1 spg cells under high glucose conditions. CLU overexpression repressed autophagy and alleviated testicular damage in diabetic rats, which was also abrogated by LY294002 treatment. Conclusions: CLU expression is suppressed during diabetes‐induced testicular damage, whereas CLU overexpression alleviates diabetes‐induced testicular damage by activating PI3K/AKT/mTOR signalling to inhibit autophagy and further repress spermatogenic cell apoptosis. Abstract : Research article : A diagram depicting the mechanism of Clusterin suppresses spermatogenic cell apoptosis to alleviate diabetes‐induced testicular damage by inhibiting autophagy via the PI3K/AKT/mTOR axis.